Minimizing maladaptations derived from tennis serve training and competition loads - Colomar, J.; Peña, J.; Vicens-Bordas, J.; Baiget, E. (Strength and Conditioning Journal, 2024)
Junior tennis players perform many high-intensity serves during practice and competition. These demands can potentially put specific musculoskeletal structures at risk of developing negative adaptations that can increase the likelihood of injury. In addition, serve velocity enhancement sessions commonly include motion-specific resistance training approaches that can increase the load on these already at-risk muscles and joints. Therefore, it is essential to address holistically the optimization of serve training. To minimize harmful musculoskeletal adaptations and maximize performance, a multiperspective approach is advised when designing a serve training program for junior tennis players. This paper will propose methodological recommendations that can be included in these programs. Examples and suggestions include the benefits of incorporating general strength training tasks to minimize asymmetries and build robustness. Furthermore, on-court injury prevention protocols are proposed to target specific altered body structures and overall serving loads. Finally, load management strategies should ensure that training is controlled and organized appropriately.